Effects of music on resistance exercise performance: a narrative review - Grgic, J. (Strength and Conditioning Journal, 2022)
This review aimed to summarize and critically evaluate the research on the effects of music on resistance exercise performance. Research in the field has consistently demonstrated an ergogenic effect of music on resistance exercise performance. Specifically, studies have reported that listening to music pre-exercise or during exercise may enhance handgrip strength, muscle endurance, velocity, and power. Although a performance-enhancing benefit has been observed in many (but not all studies), several factors such as music tempo, volume, and genre preference may modulate the ergogenic effect of music. An ergogenic effect is commonly reported with faster tempo music (>120 bpm) set to muscle volume of 70-80 decibels. Using individual preference regarding music genre seems to produce the most consistent performance-enhancing effect. Besides these factors, lyrical content, harmony, and melody are also factors that may determine the ergogenic potential of music. By using some of the recommendations outlined herein, individuals may harness and optimize the ergogenic effects of music on resistance exercise performance.